Histological Evaluation and Management of Rare Case of Supernumerary “Ghost” Teeth - Dino Re; Elena Canciani; Corinne Poli; Laura Buccarella; Marilisa Toma; Andrea Carlo Butti; Claudia Dellavia (Case Reports in Dentistry)
Supernumerary teeth are teeth that exceed the normal dental formula. Their prevalence in the permanent dentition is 1–14% and they occur more frequently in maxilla with a sex ratio of 2 : 1 in favor of males. They are often associated with syndromes but there are examples of nonsyndromic multiple supernumerary teeth reported in the literature. CBCT is usually the best exam for radiographic diagnosis and treatment planning, because it provides 3D information about location and morphology of supernumerary teeth. This paper reports a rare case of four supernumerary teeth in a nonsyndromic 9-year-old boy. The peculiarity of this case is that two more exceeding teeth were found during surgical procedure. After extraction, all the teeth underwent a histological undecalcified processing for light microscopical examination. The two “ghost” supernumerary teeth seemed to be primordial dental germs, possibly resulting from an altered odontogenic process. After supernumerary teeth extraction, X-rays and exfoliation monitoring are recommended, since permanent retained teeth often erupt naturally or, at least, improve their condition. Radiographic follow-up is also useful in order to assess the formation of further teeth due to the hyperactivity of the dental lamina.